Malay philologists’ acceptance of an e-workspace to support teaching, learning and researching manuscripts - Zulkifli, Zahidah; Abdullah, Noorhidawati; Awang Ngah, Zainab (Faculty of Computer Science and Information Technology, Universiti Malaya, 2014)
This paper reports on the user evaluation to examine participants’ acceptance of an e-workspace that has been developed to support the process of teaching, learning and researching manuscripts in the Malay manuscript community. This evaluation is conducted to answer the following research question: a) What is the perceived usefulness of the e-workspace in supporting transliteration work and collaboration from the Malay manuscript community? b) What are the usability issues highlighted regarding the Malay manuscript e-workspace? The evaluation is carried out based on five usability dimensions, namely, efficiency, effectiveness, engagement, error tolerance and ease of learning. A single case study has been employed in this evaluation which included lecturers, students, and researchers from the Academy of Malay Studies, University of Malaya as participants. These participantsare directly involved in teaching, learning and researching Malay manuscripts. The user evaluation is carried out in two phases. The first phase involves a task-based approach where participants are given several tasks to perform while using the e-workspace. The second phase is a focus group discussion to elicit the participants’ feedback on the perceived usefulness of the eworkspace after they have completed the given tasks. System evaluation of the Malay Manuscript eworkspace in serving the manuscript community has been reflected by the positive feedback from the 19 participants. The findings signify a positive reaction from participants towards the eworkspace. The e-workspace in general has been perceived as useful to support teaching, learning and researching manuscripts by providing a collaborative platform to conduct transliteration work electronically.